2018
DOI: 10.1371/journal.pone.0202522
|View full text |Cite|
|
Sign up to set email alerts
|

CD28 deficiency leads to accumulation of germinal-center independent IgM+ experienced B cells and to production of protective IgM during experimental malaria

Abstract: Protective immunity to blood-stage malaria is attributed to Plasmodium-specific IgG and effector-memory T helper 1 (Th1) cells. However, mice lacking the costimulatory receptor CD28 (CD28KO) maintain chronic parasitemia at low levels and do not succumb to infection, suggesting that other immune responses contribute to parasite control. We report here that CD28KO mice develop long-lasting non-sterile immunity and survive lethal parasite challenge. This protection correlated with a progressive increase of anti-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Although the majority of high IgM responses (RI> 3) were no longer detected in the low transmission period, the results suggest that individuals in P. vivax-endemic Amazonian communities were able to sustain their DBPII-specific IgM antibody responses. These results may explain recent findings showing that IgM-expressing memory B cells are expanded in malaria patients living in endemic areas [27], and confirm data from other studies, which suggest that IgM antibodies may play an underappreciated role in immune response against malaria infections [29][30][31]. Although scant longitudinal data are available about secondary IgM responses in P. vivax-exposed populations, a recent prospective study undertaken in a low transmission area of Western India demonstrated that P. vivax alters peripheral B-cell profiles and induces https://doi.org/10.1371/journal.pone.0232786.g003…”
Section: Plos Onesupporting
confidence: 90%
See 2 more Smart Citations
“…Although the majority of high IgM responses (RI> 3) were no longer detected in the low transmission period, the results suggest that individuals in P. vivax-endemic Amazonian communities were able to sustain their DBPII-specific IgM antibody responses. These results may explain recent findings showing that IgM-expressing memory B cells are expanded in malaria patients living in endemic areas [27], and confirm data from other studies, which suggest that IgM antibodies may play an underappreciated role in immune response against malaria infections [29][30][31]. Although scant longitudinal data are available about secondary IgM responses in P. vivax-exposed populations, a recent prospective study undertaken in a low transmission area of Western India demonstrated that P. vivax alters peripheral B-cell profiles and induces https://doi.org/10.1371/journal.pone.0232786.g003…”
Section: Plos Onesupporting
confidence: 90%
“…Here, we demonstrated that long-term P. vivax exposure to low and unstable levels of malaria transmission can lead to a sustained DBPII-specific IgM response. At this time, it is not possible to define if this persistent DBPII-related IgM response could indicate that IgM-experienced B cells needs to be constantly activated or if this response is rather associated with a bona-fide memory [29,46]. Of relevance, P. falciparum-specific IgM antibodies were detected for more than 6 months in Australians returning from malaria endemic areas [31].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…To test this hypothesis, we measured antibody titers against a truncated carboxy terminus of the blood-stage antigen merozoite surface protein (MSP1) shown to be critical for infection by ELISA [ 24 ]. We decided to measure specifically the IgG 2 c because the IgG2 c antibody appears early in plasma and can confer protection in murine models of blood-stage malaria [ 58 60 ]. Furthermore, we decided to measure acute antibody titers immediately prior to divergence of parasite burden between Ifnlr1 −/- mice and littermate controls, given that variations in inoculum and ongoing inflammation can have dramatic effects on antibody titers during infection with malaria [ 24 ] and other pathogens [ 61 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…These lower affinity memory cells likely allow for a secondary response to a broad range of pathogen variants, whereas germinal center-derived high affinity memory cells are more tailored toward responding to reinfection with the original challenge (4,6,7,78). Early IgM memory cells are known to be important in several mouse models of infectious disease, including infection with Ehrlichia muris, a tick-borne intracellular bacteria (79,80), and malaria (81,82). Mice with specific defects in extrafollicular responses, such as those lacking PIK3IP1 in B cells described in this study, may serve as a useful model to study these diseases.…”
Section: Discussionmentioning
confidence: 99%